2021
DOI: 10.1111/jpc.15330
|View full text |Cite
|
Sign up to set email alerts
|

Managing low‐risk febrile neutropenia in children in the time of COVID‐19: What matters to parents and clinicians

Abstract: Aim The Australian ‘There is no place like home’ project is implementing a paediatric low‐risk febrile neutropenia (FN) programme across eight paediatric hospitals. We sought to identify the impact of the coronavirus disease 2019 (COVID‐19) pandemic on programme implementation. Methods Paediatric oncology, infectious diseases and emergency medicine health‐care workers and parent/carers were surveyed to explore the impact of the COVID‐19 pandemic on home‐based FN care. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 18 publications
(35 reference statements)
0
26
0
1
Order By: Relevance
“…Discrete choice experiments that have examined treatment preferences of parents with children undergoing active cancer treatment have found that many parents still prefer inpatient management over outpatient management for low-risk FN episodes [ 4 , 6 ], whilst parents who valued HRQoL were more likely to opt for outpatient care [4] . More recently, a clear preference for home-based treatment of low-risk FN was identified by clinicians and parents due to perceived improvements in HRQoL [28] . This highlights the importance of consumer engagement when home-based FN care pathways are developed and implemented to ensure that parent and patient concerns and reservations are appropriately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Discrete choice experiments that have examined treatment preferences of parents with children undergoing active cancer treatment have found that many parents still prefer inpatient management over outpatient management for low-risk FN episodes [ 4 , 6 ], whilst parents who valued HRQoL were more likely to opt for outpatient care [4] . More recently, a clear preference for home-based treatment of low-risk FN was identified by clinicians and parents due to perceived improvements in HRQoL [28] . This highlights the importance of consumer engagement when home-based FN care pathways are developed and implemented to ensure that parent and patient concerns and reservations are appropriately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] A recent survey of parents of children with cancer and FN similarly identified strong themes of perceived wellbeing, and reduced impact on the family due to home-based care. 21 However, these qualitative data are captured infrequently, and more attention should be directed towards routinely embedding QoL measures in paediatric research as well as to understand the most effective method of obtaining reliable information from children and their families. By incorporating a broader perspective in our analysis, we are able to show the value of the home-based FN programme from the families' viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Although these numbers were small, our evaluation took this into account to reflect the real‐world application of the programme. The feasibility of safely treating higher risk patients through the programme, together with increasing clinician acceptance in managing cancer patients at home, 21 has prompted a programme update. Currently, all children with FN, irrespective of underlying FN risk status, may be considered for home‐based care, provided HITH‐eligibility criteria are fulfilled and a minimum in‐hospital observation complied with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora a atual pandemia pela COVID-19 tenha tido pouco impacto no nível de confiança e interesse, contribuído para mudanças na atenção de cuidados a crianças com câncer, que em geral melhorou a aceitabilidade desse modelo de atenção. Para facilitar o atendimento domiciliar destacou a importância da segurança, infraestrutura hospitalar, comunicação e conhecimento das evidências como fatores-chave para os profissionais de saúde (Haeusler et al, 2021).…”
Section: Categoria 1) Recomendações Para Crianças Com Câncer No Contexto Da Pandemiaunclassified